NMR Structure Elucidation of Naphthoquinones from Quambalaria cyanescens - Procházková, Eliška; Kucherak, Oleksandr; Stodůlková, Eva; Tošner, Zdeněk; Císařová, Ivana; Flieger, Miroslav; Kolařík, Miroslav; Baszczyňski, Ondřej (Journal of natural products, 2021)
Naphthoquinones isolated from Quambalaria cyanescens (quambalarines) are natural pigments possessing significant cytotoxic and antimicrobial properties. Determining the structure of naphthoquinone compounds is important for the understanding of their biological activities and the informed synthesis of related analogues. Identifying quambalarines is challenging, because they contain a hydroxylated naphthoquinone scaffold and have limited solubility. Here, we report a detailed structural study of quambalarine derivatives, which form strong intramolecular hydrogen bonds (IMHBs) that enable the formation of several tautomers; these tautomers may complicate structural investigation due to their fast interconversion. To investigate tautomeric equilibria and identify new quambalarines, we complemented the experimental NMR spectroscopy data with density functional theory (DFT) calculations.
Keywords: Antineoplastic Agents; Molecular Structure; Magnetic Resonance Spectroscopy; Basidiomycota; Anti-Infective Agents; molekulární struktura; magnetická rezonanční tomografie; Hydrogen Bonding; antiinfekční látky; magnetická rezonanční spektroskopie; protinádorové látky; Magnetic Resonance Imaging; vodíková vazba; Naphthoquinones; naftochinony